We Are Happy To Be Here: The Onboarding Experience in Academic Libraries. Issue 4 (18th May 2016) - Keisling, Bruce; Laning, Melissa
ABSTRACT: This study looks at the organizational entry or onboarding experience of 20 new academic librarians through a series of interviews. The goal is to explore what new librarians in a variety of settings and career stages consider most important for them to learn during onboarding and the best approaches for sharing information with them. The study also explores how much institutions are actively learning about the signature strengths of new employees as part of the onboarding process. The authors conclude with recommendations for additional research and onboarding process improvements.